Tele-pharmacy Anticoagulation Clinic During COVID-19 Pandemic: Patient Outcomes - Al Ammari, Maha; AlThiab, Khalefa; AlJohani, Manal; Sultana, Khizra; Maklhafi, Nada; AlOnazi, Hayel; Maringa, Aswaq (Frontiers in Pharmacology, 2021)
Introduction It is well-established that clinical pharmacist-managed anticoagulation services achieve superior anticoagulation control, with a positive impact. At King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia, the structure of anticoagulation management is a pharmacist-managed specialty service. With the current COVID-19 situation, measures were taken to assure the continuity of patient care by establishing Tele-pharmacy anticoagulation clinics. Materials and Methods This was a prospective study with patients prescribed anticoagulation and followed-up for three months. Since establishing the anticoagulation virtual clinic in March 2020, 270 patients were recruited in the study. The data collected included age, gender, co-morbidities, indication for anticoagulation, intended duration of treatment, warfarin dose, testing of International Normalized Ratio (INR), INR target, range of INR values, time INR was within the therapeutic range (TTR), complications of therapy (bleeding and/or bruises). The patients were asked to complete the Pharmacist satisfaction survey (PSS) after their consultation to assess patient satisfaction with the new virtual consultation system. Linguistic and cultural validation was conducted for the questionnaire. Results A total of 270 patients were included in the study. The mean percentage of overall INR values in the range was 59.39% ± 32.84, and the mean time with the overall INR within the therapeutic range 57.81% ± 32.08. Thirty-one percent of the sample had good anticoagulation control (time in therapeutic range > 70%). The median satisfaction score was 32 (IQR 28-36) with a maximum score of 40. Conclusion: This is the first study to assess the tele-pharmacy anticoagulation clinic’s efficiency and patient satisfaction in Saudi Arabia during the COVID-19 pandemic. This type of consultation was as effective as face-to-face consultations. The study also highlighted that though the reduction in the cost of care was not substantial, there was a significant increase in resource (clinical pharmacist) utilization as a result of this model. The adoption of tele- resulted in time savings for the clinical pharmacists who can be utilized in many other improvement projects in adult ambulatory clinics to ensure the delivery of better quality and safe patient care.